นวนิยายเรื่อง ‘ล่า’ ของทมยันตี: การตีความและการเล่นทางภาษากับชื่อของตัวละครเอกหญิง - Hongthong , Direk (Journal of Social Sciences and Humanities Research in Asia, 2020)
This paper aims to study Thommayantee’s Novel “La (Hunt)” in terms of the interpretation and speech play of the female leading character’s names: “Mathusorn” and “Rungrudee,” respectively. The study reveals that the interpretation by dissecting the character’s name into 2 parts, “Mathu (nectar, honey) and sorn (arrow, gun),” discloses the female leading character’s two sides of personalities: the exposed side -- well-behaved, gentle and as sweet as honey, and the hidden side -- as ferocious as a lethal weapon. Meanwhile, the interpretation of another name, “Rung (bright) and rudee (mind),” reveals the speech play of its meaning in the worldly aspect. That is, Rungrudee’s mind is “bright” only at plotting to take revenge; however, she could not enlighten herself in the spiritual aspect. This is the reason why her life faces the tragic end. The results of this study reflect the author’s artfulness in naming the leading character in order to challenge the readers’ thinking and develop their understanding of life on the Buddhist path. Key words: Interpretation of character’s name, speech play, Thommayantee, Buddhist concepts in Thai literary works